PENGARUH ONLINE CUSTOMER REVIEW, CELEBRITY ENDORSER DAN BRAND IMAGE TERHADAP PURCHASE DECISION PRODUK THE ORIGINOTE PADA PLATFORM TIKTOK - Vivian Hartanto; Nur Amalyna Yusrin (Publika Citra Media, 2026)
The purpose of this study is to identify various factors that influence TikTok users' decisions to purchase The Originote products, including online customer reviews, celebrity endorsements, and brand image. The method used is quantitative. This study was conducted in Tangerang Regency. A total of 150 participants were interviewed using a Likert scale questionnaire. The analysis technique used in this study was multiple linear regression analysis and hypothesis testing with the F test and t test as data analysis techniques used. The results of the study indicate that online customer reviews, celebrity endorsers, and brand image have a simultaneous effect on purchase decisions. Online customer reviews and brand image have a partial effect on purchase decisions, while celebrity endorsers have no partial effect on purchase decisions.